Parasite communities of freshwater fish under flood conditions - Kadlec, Dusan; Simková, Andrea; Jarkovský, Jirí; Gelnar, Milan (Parasitology research, 2003)
The parasite communities of the freshwater fish species roach ( Rutilus rutilus), bitterling ( Rhodeus sericeus amarus) and perch ( Perca fluviatilis) were investigated during a major flood. Differences in parasite community structure due to changes in the host environment were expected. We therefore tested for differences in parasite species abundance and diversity as a consequence of the flood. Potential changes in parasite community structure due to seasonal influences were also considered. We found differences in the composition of parasite species and the proportion of ecto- and endoparasites in the three host species. The parasite community of roach was richer in species than those of perch and bitterling. Roach harboured more ectoparasite than endoparasite species. Parasite communities of both perch and bitterling were richer in endoparasite species and had a lower number of ectoparasite species. Parasite communities of the three different host species responded in different ways to environmental change. Considering all parasite species, no effect of either season or flood was found on the species diversity in either perch or bitterling. The flood caused an increase in the parasite species diversity in roach. For roach and perch, higher parasite abundance were found before the flood compared to after flood. However, no difference was found between the different seasons after the flood. By contrast, bitterling had the highest parasite abundance in the season after the flood. When analysing ecto- and endoparasites separately, a decrease in ectoparasite abundance was found in roach and perch, probably related to the flood, and due mainly to a decrease in monogenean species. A significant increase in the abundance of endoparasites was found in perch. In bitterling, the post-flood increase in ectoparasites was due to a high abundance of Gyrodactylus spp. We conclude that the parasite communities of the three fish species responded in different ways to the flood. This may be due to changes in the host life history strategy or in the immune response in conditions of stress.
Keywords: Animals; Seasons; paraziti; Perches; okounovití; Cyprinidae; Host-Parasite Interactions; Fishes; interakce hostitele a parazita; roční období; ryby; Parasites; Fresh Water; sladká voda; Czech Republic; Disasters; katastrofy; ekosystém; Česká republika; Ecosystem; zvířata